2016
DOI: 10.7150/ijms.13456
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity Analysis According to Sex and Age in Hypertension Patients in China

Abstract: Background: Hypertension, an important risk factor for the health of human being, is often accompanied by various comorbidities. However, the incidence patterns of those comorbidities have not been widely studied.Aim: Applying big-data techniques on a large collection of electronic medical records, we investigated sex-specific and age-specific detection rates of some important comorbidities of hypertension, and sketched their relationships to reveal the risk for hypertension patients.Methods: We collected a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 38 publications
2
26
1
2
Order By: Relevance
“…Up to 46.9% hypertensive patients had at least one comorbidity in 2017 and 31% of them experienced new comorbidities within two years. Through the Chinese National Surveillance System, the most common comorbidity of hypertension was coronary heart disease, with detection rates of 21.71%, while 7.53% had cerebral infarction which ranked fifth [25]. In contrast, the incidence of stroke (22.3%) was particularly high, while coronary heart disease (6.4%) was relatively lower in our study.…”
Section: Resultscontrasting
confidence: 50%
“…Up to 46.9% hypertensive patients had at least one comorbidity in 2017 and 31% of them experienced new comorbidities within two years. Through the Chinese National Surveillance System, the most common comorbidity of hypertension was coronary heart disease, with detection rates of 21.71%, while 7.53% had cerebral infarction which ranked fifth [25]. In contrast, the incidence of stroke (22.3%) was particularly high, while coronary heart disease (6.4%) was relatively lower in our study.…”
Section: Resultscontrasting
confidence: 50%
“…To make our investigation more comprehensive, we also analyzed diabetes mellitus 22-24 and hyperlipidemia 20, 25 as hypertension's comorbidities. The reason why those two diseases were chosen as hypertension's major comorbidities was because, just like hypertension, those two diseases were also were considered strong indicating factors of coronary heart disease 26.…”
Section: Introductionmentioning
confidence: 99%
“…Hidalgo et al studied phenotypic networks and found that patients with diseases highly connected tend to die sooner 7 . This tool has been used to identify comorbidity associated with hypertension 8 , chronic pulmonary obstructive disease 9 or mental disease 10 and to compare multimorbidity by gender 11 . Most of the studies used hospital databases to construct the networks.…”
mentioning
confidence: 99%